COMMON ERRORS MADE BY PMC STUDENTS AT EEC (EFFECTIVE ENGLISH COURSE) JOMBANG IN PRONOUNCING ENGLISH SILENT-LETTERS - Fanani, Achmad; Mawardi, Mohammad Yazid (Educate, 2012)
Abstract Interference is the influence of first language (L1) into second language (L2)(negative interlingual transfer) that generally leads to errors. Thus the mother tongue of first language in fact interferes to the second language. Besides, markedness is the obvious factor contributing the errors as well. This study investigates the interference of Indonesian language (L1) into the English language acquisition commonly made by PMC, Prospective Model Class, students at Effective English Course (EEC) Jombang. More specifically, this study describes the influence of Indonesian pronunciation into English pronunciation acquisition that causes errors and the language-based factors that influence the occurrence of interference. The result of this research shows that the errors related to the interference of L1 are categorized into 12 kinds of errors: pronouncing silent ‘b’, pronouncing silent ‘c’, pronouncing silent ‘d’, pronouncing silent ‘g’, pronouncing silent ‘gh’, pronouncing silent ‘h’, pronouncing silent ‘k’, pronouncing silent ‘l’, pronouncing silent ‘p’, pronouncing silent ‘s’, pronouncing silent ‘t’, and pronouncing silent ‘w’. Keywords: L1 interference, markedness, PMC students